Development of a Technology-Based Cooperative Learning Model to Improve Elementary Students’ Critical Thinking Skills - Zulfiati, Heri Maria; Biya Ebi Praheto; Thadius Marhendra Adi Kristanto; Alisa Maharani Husaen (UIN Sunan Kalijaga Yogyakarta, 2025)
The rapid development of digital technology requires elementary schools to provide learning experiences that foster critical thinking skills from an early age. However, instructional practices in many elementary classrooms are still dominated by teacher-centered approaches, which limit student engagement and opportunities for higher-order thinking. This study aims to develop and validate a technology-based cooperative learning model that aligns with the characteristics of elementary school students and is oriented toward enhancing critical thinking skills. This research employed a Research and Development (R&D) approach, consisting of a preliminary study, model design, expert validation, revision, and a limited field trial involving fifth-grade students. The developed model integrates cooperative learning strategies, specifically Think-Pair-Share and Jigsaw, supported by digital technologies such as Google Classroom, Padlet, and Kahoot, to facilitate collaboration, reflective discussion, and formative assessment. Research instruments included expert validation sheets, observation checklists, and critical thinking skills tests.The validation results indicate that the developed model is highly valid and feasible for implementation. The field trial results demonstrate increased student engagement, improved conceptual understanding, and higher critical thinking scores compared to previous instructional conditions. These findings suggest that the technology-based cooperative learning model has strong potential to support the development of critical thinking skills in elementary education and provides a practical framework for teachers to integrate technology into classroom instruction.